The receptor for advanced glycation end products impairs host defense in pneumococcal pneumonia - van Zoelen, Marieke A D; Schouten, Marcel; de Vos, Alex F; Florquin, Sandrine; Meijers, Joost C M; Nawroth, Peter P; Bierhaus, Angelika; van der Poll, Tom (The Journal of immunology (1950), 2009)
Streptococcus pneumoniae is the most common cause of community-acquired pneumonia. The receptor for advanced glycation end products (RAGE) is a multiligand receptor that is expressed ubiquitously in the lungs. Engagement of RAGE leads to activation of multiple intracellular signaling pathways, including NF-kappaB and subsequent transcription of several proinflammatory mediators. To determine the role of RAGE in the innate immune response to S. pneumoniae pneumonia, RAGE-deficient (RAGE(-/-)) and wild-type mice were intranasally inoculated with S. pneumoniae. S. pneumoniae pneumonia resulted in an up-regulation of constitutively present RAGE expression in lung tissue, especially in the interalveolar septae. RAGE(-/-) mice showed an improved survival, which was accompanied by a lower bacterial load in the lungs at 16 h and a decreased dissemination of the bacteria to blood and spleen at 16 and 48 h after inoculation. RAGE(-/-) macrophages showed an improved killing capacity of S. pneumoniae in vitro. Lung inflammation was attenuated in RAGE(-/-) mice at 48 h after inoculation, as indicated by histopathology and cytokine/chemokine levels. Neutrophil migration to the lungs was mitigated in the RAGE(-/-) mice. In addition, in RAGE(-/-) mice, activation of coagulation was diminished. Additional studies examining the effect of RAGE deficiency on the early (6-h) inflammatory response to S. pneumoniae did not reveal an early accelerated or enhanced immune response. These data suggest that RAGE plays a detrimental role in the host response to S. pneumoniae pneumonia by facilitating the bacterial growth and dissemination and concurrently enhancing the pulmonary inflammatory and procoagulant response.